Governance guidance for an eRegistry for maternal and child health: lessons from the occupied Palestinian territory. (21st February 2018) - Myhre, Sonja; Ghanem, Buthaina; Salman, Rand; Kaye, Jane; Frøen, J Frederik
Abstract: Background: The eRegistry for maternal and child health is an electronic registry system developed for the collection, analysis, retrieval, storage, and dissemination of information on health determinants and outcomes for women and children. The purpose of the eRegistry is to improve health-care provision and public health surveillance in the occupied Palestinian territory. Given the highly sensitive nature of reproductive health information, however, careful attention to ethical and legal considerations is essential. The aim of this study was to map the legal, regulatory, and ethical landscape using a situation analysis tool tailored for the Palestinian context and to identify gaps, opportunities, and actions necessary to ensure an ethical and lawful framework for an eRegistry. Methods: We used an exploratory situation analysis tool (SAT) to map the current legislative, regulatory, and governance environment in the occupied Palestinian territory. The primary objective was to assess, document, and analyse the legal and ethical landscape. Specific focal topics addressed by the SAT included identifying relevant legislation (eg, civil registration, data privacy, health registries, public health law), existing governance structures, accountability, and oversight bodies (ie, ethical review committees, data protection authorities), and data quality and security policies. The Palestinian National Institute of Public Health (PNIPH) completed the SAT and held workshops for relevant stakeholders, including staff from the ministry of health's legal affairs department, PNIPH staff, and other legal experts. No ethical approval was required because data were collected from public documents. Findings: The findings from the SAT reflect the current situation in the occupied Palestinian territory with respect to existing laws, accountability and oversight bodies, and data collection protocols and policies concerning data privacy and security. Existing Palestinian legislation relevant to health registries includes Article 4 of the General Statistics Law (2000), which honours data confidentiality and the privacy of individuals. The Penal Law number 16 of 1960 addresses the disclosure of confidential information, whereas Article 355 specifically states that disclosure of official confidential information to unauthorised persons is unlawful and could result in imprisonment. Furthermore, the Public Health Law (2004) addresses general maternal and child health issues in Articles 4 and 5. We investigated relevant oversight and accountability bodies (eg, ethical review board) that might be relevant to an electronic maternal and child health registry. Finally, in a review of existing data privacy protocols and policies, we noted that few formal protocols (ie, privacy manual) or policies regulate data collection and access practices. Interpretation: Specific areas within the legal and regulatory framework of the occupied Palestinian territory could be strengthened. The eRegistry Governance Guidance Toolkit, predicated on the SAT content, outlines responsible data stewardship practices and provides assistance in developing protocols and policies in lieu of specific laws by providing a framework to ensure the protection of women and children's privacy. Effective governance that protects women and children's privacy and confidentiality is essential for maintaining public trust and ensuring the long-term success of an eRegistry. Funding: European Research Council and the Norwegian Agency for Development Cooperation (Norad).